PENINGKATAN KINERJA PEMASARAN MELALUI DIGITAL MARKETING, INOVASI DAN ORIENTASI PASAR - Achmad Solechan; Kusumo, Haryo; Shibghatalloh, Ahmad Hafiyyan; Wardhani, Arisanti Ayu; Syafrudin, Hasan Aminda; Arwinda, Sherly (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
In the digital era, digital marketing has become the main strategy for MSMEs to increase competitiveness. This study analyzes the influence of digital marketing, product innovation, and market orientation on MSME marketing performance. The method used is a literature review of various previous studies to identify the relationship between variables. The results of the study indicate that digital marketing expands market reach and increases promotion effectiveness, but its effectiveness depends on product innovation and marketing strategy. Product innovation increases competitiveness, while market orientation helps understand customer needs. This study highlights the need for integration of these three factors to optimize MSME marketing performance and provide insights for business actors and academics.